Review and prospects of allocation efficiency of strategic metal resources across entire industry chain in the context of new quality productive force development - Xuehong, ZHU; Zhipeng, LIANG; Anqi, ZENG; Yu, DONG; Ruiqi, ZHU; Shenbin, LUO (Zi yuan ke xue, 2025)
[Objective] Strategic metal resources are key production factors in cultivating new quality productive forces. Improving the allocation efficiency of these resources has become an essential requirement and a key approach for developing new quality productive forces. However, traditional development approaches have resulted in the current allocation efficiency of strategic metal resources facing serious challenges in promoting the development of new quality productive forces. [Methods] Based on relevant literature from 1996 to 2025, this study systematically reviews the evaluation methods, driving factors, and improvement pathways of allocation efficiency of strategic metal resources across the entire industry chain in the context of the development of new quality productive forces. [Results] (1) Traditional evaluation methods for resource allocation efficiency mainly analyze single or multiple stages of the industry chain, but fail to systematically examine allocation efficiency from the perspective of the entire industry chain. This may lead to biased assessments of the allocation efficiency of strategic metal resources. (2) Existing studies consider factors such as economic, technological, policy, and social influences on resource allocation efficiency. However, in the context of new quality productive force development, it is necessary to comprehensively examine both traditional and emerging factors, focusing on their heterogeneous and synergistic impacts across different stages of the industrial chain. In-depth research on emerging factors is also needed. (3) Existing approaches to improving the allocation efficiency of strategic metal resources across the entire industrial chain are primarily based on single-policy measures and qualitative analysis. In the context of new-quality productive force development, these pathways should take into account the coordination and compatibility among various policy tools. [Conclusion] To meet the demands of new quality productive force development, future research should integrate the “economic-environmental-social” system coupling framework and construct multiple hybrid models to evaluate the allocation efficiency of strategic metal resources. On this basis, a combination of multiple models and objective data should be used to test the effects of driving factors and improvement pathways. This study provides a scientific and effective improvement pathway for enhancing the allocation efficiency of strategic metal resources across the entire industry chain and for the development of new quality productive forces.